Reinventing industrial strategy: The role of government policy in building industrial competitiveness. - Lall, S (QEH, 2003)
The paper reviews the nature of current globalization and the growing divergence in competitive performance in the developing world. It considers the case for industrial policy, contrasting the neoliberal with the structuralist approach. It argues that there is a valid case for selective interventions in overcoming the market and institutional failures in building the capabilities required for industrial development. It describes the strategies adopted by the Asian Tigers to build industrial competitiveness, and concludes with lessons for other developing countries. The kinds of industrial policy needed in the current setting are different from traditional industrialisation strategies, but globalization and technical change do not eliminate the need for intervention. On the contrary, given path dependence, cumulativeness and agglomeration economies, they increase it. There is a need to reconsider the rules of the game constraining the exercise of industrial policy, and for international assistance in designing and implementing appropriate policies.